International Learner Perceptions, Educational Value, and Cost Associated With the Use of Start-to-Finish Surgical Simulation Compared With Cadaveric Models. Issue 2 (28th February 2023) - Damon, Aaron; Lee, Seung Jin; Pichelmann, Mark; Nottmeier, Eric; CreveCoeur, Travis S.; Clifton, William
Abstract : BACKGROUND: Graduate surgical education is highly variable across regions and institutions regarding case volume and degree of trainee participation in each case. Dedicated educational curriculum using cadaveric tissue has been shown to enhance graduate surgical training, however with associated financial and utility burden to the institution. OBJECTIVE: To investigate the utility of educational and cost applications of a novel method of combining mixed organic hydrogel polymers and 3-dimensional printed anatomic structures to create a complete "start-to-finish" simulation for resident education in spinal anatomy, instrumentation, and surgical techniques. METHODS: This qualitative pilot study investigated 14 international participants on achievement of objective and personal learning goals in a standardized curriculum using biomimetic simulation compared with cadaveric tissue. A questionnaire was developed to examine trainee evaluation of individual anatomic components of the biomimetic simulators compared with previous experience with cadaveric tissue. RESULTS: A total of 210 responses were acquired from 14 participants. Six participants originated from US residency education programs and 8 from transcontinental residency programs. Survey results for the simulation session revealed high user satisfaction. Score averages for each portion of the simulation session indicated learner validation of anatomic features for the simulation compared with previous cadaveric experience. Cost analysis resulted in an estimated savings of $10 833.00 for this single simulation session compared with previous cadaveric tissue sessions. CONCLUSION: The results of this study indicate a strong potential of establishing biomimetic simulation as a cost-effective and high-quality alternative to cadaveric tissue for the instruction of fundamental spine surgical techniques. Abstract :